2013
DOI: 10.1021/es304579s
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation Mechanisms of a Branched Nonylphenol Isomer in Soil-Derived Organo–Clay Complexes during a 180-Day Experiment

Abstract: The incorporation process of a defined (13)C- and (14)C-labeled nonylphenol isomer (4-(3,5-dimethylhept-3-yl)phenol) into soil-derived organo-clay complexes was investigated. Isolated organo-clay complexes were separated into humic subfractions. Noninvasive ((13)C-CP/MAS NMR) and invasive methods (sequential chemical degradation, pyrolysis) were applied to obtain detailed information about the mode of incorporation, chemical structure, and change of the incorporation character of nonextractable residues in cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Selective chemical cleavage of covalent bonds, followed by identification of the released products may provide information about the nature of the bound residues. In this manner, Richnow et al , found ester- and ether-linked residues of polycyclic aromatic hydrocarbons in soil, Martens quantified the composition and concentration of ester- and ether-linked phenolic acids in plants and soils, and Riefer et al revealed that reversible ester (amine) linkages are responsible for binding of nonylphenol residues to soil humic substances. Recently, Liu et al .…”
Section: Introductionmentioning
confidence: 99%
“…Selective chemical cleavage of covalent bonds, followed by identification of the released products may provide information about the nature of the bound residues. In this manner, Richnow et al , found ester- and ether-linked residues of polycyclic aromatic hydrocarbons in soil, Martens quantified the composition and concentration of ester- and ether-linked phenolic acids in plants and soils, and Riefer et al revealed that reversible ester (amine) linkages are responsible for binding of nonylphenol residues to soil humic substances. Recently, Liu et al .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review, these attempts have been summarized . As a conclusion, NER can be differentiated into xenobiotic residues, either entrapped (type I NER) in the structural voids of the soil, covalently bound to humic matter (type II NER), or so-called biogenic residues (type III NER). Carbon or nitrogen from certain pesticides can be used by metabolic or cometabolic degradation for synthesis of the cell constituents of microorganisms, for example, amino acids, fatty acids. After the death and cell lysis, these compounds are incorporated into SOM forming ultimately biogenic residues .…”
Section: Introductionmentioning
confidence: 99%
“…The bound residues in NAS (Figure ) could have been formed by incorporation of TBBPA and the phenolic TPs into the organic matter in NAS via ether and ester bonds. These coupling mechanisms have also been suggested for both the biotic and abiotic formation of bound residues of phenolic compounds, such as nonylphenol and humus monomers, to soil organic matter. The absence of the active bromohydroquinone (compound 3 ) in NAS can be attributed to its chemical reaction with organic matter in NAS, as in the case of hydroquinone to soil organic matter, which likewise contributed to bound-residue formation.…”
Section: Results and Discussionmentioning
confidence: 93%